Strategies for improving drug delivery: nanocarriers and microenvironmental priming. (3rd July 2017) - Khalid, Ayesha; Persano, Stefano; Shen, Haifa; Zhao, Yuliang; Blanco, Elvin; Ferrari, Mauro; Wolfram, Joy
ABSTRACT: Introduction : The ultimate goal in the field of drug delivery is to exclusively direct therapeutic agents to pathological tissues in order to increase therapeutic efficacy and eliminate side effects. This goal is challenging due to multiple transport obstacles in the body. Strategies that improve drug transport exploit differences in the characteristics of normal and pathological tissues. Within the field of oncology, these concepts have laid the groundwork for a new discipline termed transport oncophysics. Areas covered : Efforts to improve drug biodistribution have mainly focused on nanocarriers that enable preferential accumulation of drugs in diseased tissues. A less common approach to enhance drug transport involves priming strategies that modulate the biological environment in ways that favor localized drug delivery. This review discusses a variety of priming and nanoparticle design strategies that have been used for drug delivery. Expert opinion : Combinations of priming agents and nanocarriers are likely to yield optimal drug distribution profiles. Although priming strategies have yet to be widely implemented, they represent promising solutions for overcoming biological transport barriers. In fact, such strategies are not restricted to priming the tumor microenvironment but can also be directed toward healthy tissue in order to reduce nanoparticle uptake.